2012
DOI: 10.1039/c2cc17815j
|View full text |Cite
|
Sign up to set email alerts
|

A trans diacyloxylation of indoles

Abstract: A trans diacyloxylation of indoles is accomplished by employing PhI(OAc)(2) as the oxidant. A broad range of functional groups are well tolerated. Both the electronic properties of the N-protecting groups of indoles and the acidity of the reaction media play important roles in the selectivity of indole acyloxylation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…After provingt he high activity of the new catalytic system in the CÀHa cetoxylation of benzene, we evaluated different substituteda renes ( Table 3). [16] PhI(OAc) 2 was used as the oxidant for all substrates and we comparedt he conditions without (conditions A) or with 6-fluoropicolinic acid (conditions B) for each substrate.…”
mentioning
confidence: 99%
“…After provingt he high activity of the new catalytic system in the CÀHa cetoxylation of benzene, we evaluated different substituteda renes ( Table 3). [16] PhI(OAc) 2 was used as the oxidant for all substrates and we comparedt he conditions without (conditions A) or with 6-fluoropicolinic acid (conditions B) for each substrate.…”
mentioning
confidence: 99%
“…When R = aryl groups, both III-B and III-C are formed. Such III-C/III-B ratios increase if an electron-withdrawing substituent is introduced to the phenyl ring, which may be ascribed to the increased electrophilicity of C2 position in the intermediate III-A [25].…”
Section: Mechanistic Studymentioning
confidence: 94%
“…Further optimization of the reaction conditions found that both temperature and reaction time are crucial to the yields of the product. High temperatures or prolonged reaction time dramatically decreased the yields, probably due to the deboronation of the product by fluoride (Table 4.1, entries 1-4) [25]. The reaction medium also displayed significant influence on the outcome of this reaction.…”
Section: Reaction Of O-carboryne With Nitronesmentioning
confidence: 97%
See 1 more Smart Citation
“…The high yield of 2n in Table 2 also points to this conclusion. That is to say, the tendency of protonation on the C‐3 position decides whether the reaction can proceed smoothly 12. Besides, a metal center of the complexed intermediate was crucial.…”
Section: Methodsmentioning
confidence: 99%